ANALISIS PENGARUH KOMPENSASI DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA (Studi Pada Pegawai Di Biro Keuangan Setda Provinsi Jawa Tengah) - R. Purnama, 1342020013 (Jurnal Mahasiswa Pasca Sarjana, 2015)
Target of this research to test compensation influence and organizational climate to satisfaction of job, compensation influence, organizational climate and satisfaction work to officer performance, compensation influence and organizational climate to officer performance with satisfaction work as intervening variable. this research population is civil public servant (PNS) Bureau of Setda Provinsi Central Java counted 126 people while this research sampel is entire/all population, so that used by sampling technique is census. Technique analyse data done by using doubled linear regression. By using descriptive analysis method, instrument test that is validity test and reliabilitas and also test hypothesis. From done by analyst is this research conclude that proven compensation have an effect on positive to satisfaction of job. Organizational climate have an effect on positive to satisfaction of job. Compensation have an effect on positive to officer performance. Organizational climate have an effect on positive to officer performance. Satisfaction of Job have an effect on positive to officer performance. Satisfaction of Job do not compensation influence moderation and organizational climate to officer performance. Keyword: compensation, organizational climate, satisfaction work and officer performance